The rescue of Fannie Mae and Freddie Mac - W. Scott Frame; Andreas Fuster; Joseph Tracy; James Vickery (Federal Reserve Bank of Atlanta, 2015)
We describe and evaluate the measures taken by the U.S. government to rescue Fannie Mae and Freddie Mac in September 2008. We begin by outlining the business model of these two firms and their role in the U.S. housing finance system. Our focus then turns to the sources of financial distress that the firms experienced and the events that ultimately led the government to take action in an effort to stabilize housing and financial markets. We describe the various resolution options available to policymakers at the time and evaluate the success of the choice of conservatorship, and other actions taken, in terms of five objectives that we argue an optimal intervention would have fulfilled. We conclude that the decision to take the firms into conservatorship and invest public funds achieved its short-run goals of stabilizing mortgage markets and promoting financial stability during a period of extreme stress. However, conservatorship led to tensions between maximizing the firms' value and achieving broader macroeconomic objectives, and, most importantly, it has so far failed to produce reform of the U.S. housing finance system.
Keywords: G01; G21; H12; 330; Fannie Mae; Freddie Mac; housing finance; financial crisis; government intervention